Enhanced Expression of the Multidrug Efflux Pumps AcrAB and AcrEF Associated with Insertion Element Transposition in Escherichia coli Mutants Selected with a Fluoroquinolone - Jellen-Ritter, A. S. (American Society for Microbiology, 2001)
The development of fluoroquinolone resistance in Escherichia coli may be associated with mutations in regulatory gene loci such as marRAB that lead to increased multidrug efflux, presumably through activation of expression of the AcrAB multidrug efflux pump. We found that multidrug-resistant (MDR) phenotypes with enhanced efflux can also be selected by fluoroquinolones from marRAB- or acrAB-inactivated E. coli K-12 strains having a single mutation in the quinolone-resistance-determining region of gyrA. Mutant 3-AG100MKX, obtained from a mar knockout strain after two selection steps, showed enhanced expression of acrB in a reverse transcriptase PCR associated with insertion of IS186 into the AcrAB repressor gene acrR. In vitro selection experiments with acrAB knockout strains yielded MDR mutants after a single step. Enhanced efflux in these mutants was due to increased expression of acrEF and associated with insertion of IS2 into the upstream region of acrEF, presumably creating a hybrid promoter. These observations confirm the importance of efflux-associated nontarget gene mutations and indicate that transposition of genetic elements may have a role in the development of fluoroquinolone resistance in E. coli.